VALUE OF AGRICULTURAL EXTERNALITIES ON THE EXAMPLE OF AN AGRITOURISM FARM - Rafał Baum; Magdalena Kozera-Kowalska (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2019)
EU agricultural and agrienvironmental policies design is to improve the provision of environmental public goods and positive externalities (or to reduce negative externalities). In turn, the comprehensive identification and analysis of agricultural external economies involve a need for developing a dedicated valuation methodology. The aim of the article is to review methods of valuation of farm agritourism and an attempt to evaluate the farm’s agrotourism value (based on a case study). Considerations were based on a study of scientific literature and own research. The study focuses on presenting valuation methods for external economies, and proposes a methodology for the valuation of some illustrative positive externalities of agricultural production and of natural environmental resources regarded as public goods. The novelty of the analysis concerns its approach - a transition from theoretical considerations to the operationalization of the problem – the article presents a sample of valuation of the agri-tourism value of a farm, defined as the value of a specific location resulting from the natural beauty of the landscape and leisure services produced by environmental assets. Research (surveys among tourists) was carried out in the selected farm located, in a small village by the Baltic Sea, on the outskirts of a National Park. Analysis of the results indicate that landscape features associated with agricultural activities positively influence the demand for rural tourism. The value estimated by the Travel Cost Method (TCM) amounted to PLN 3,767,325 (approx. EUR 876 thousand). The amount shows the importance of externalities generated by the farm.